Does inflammation moderate the effect of vitamin D supplementation on depressive symptoms? Results of an interventional study in children and adolescents - Schlarbaum, Laura; Jankovic, Nicole; Bühlmeier, Judith; Hohoff, Eva; Dankers, Rhea; Engler, Harald; Hirtz, Raphael; Zwanziger, Denise; Grasemann, Corinna; Peters, Triinu; Hinney, Anke; Antel, Jochen; et al. (European Journal of Nutrition)

Does inflammation explain the association between vitamin D and depression? Results of a cross-sectional study in children and adolescents - Schlarbaum, Laura; Jankovic, Nicole; Bühlmeier, Judith; Engler, Harald; Hirtz, Raphael; Grasemann, Corinna; Peters, Triinu; Hinney, Anke; Antel, Jochen; Hebebrand, Johannes; Föcker, Manuel; Libuda, Lars (British Journal of Nutrition)
Abstract Vitamin D has been associated with depression, potentially via anti-inflammatory mechanisms, yet data is scarce, particularly in adolescence. We investigated (1) whether lower vitamin D status is associated with greater depression severity and (2) whether this association is statistically moderated by inflammation in patients of a child and adolescent psychiatry department. At admission fasting morning venous blood was drawn. Serum vitamin D (25(OH)D) and C-reactive protein (CRP) were analyzed in all participants [n=465 (64.7%♀; 11.3-18.9 years)]. In a subsample [n=177], we additionally measured tumor necrosis factor-alpha, interferon-gamma and interleukin (IL)-1β, IL-6, IL-8, IL-10. Depression severity was assessed by the Beck Depression Inventory-II (BDI-II) [n=450], the Diagnostic System for Mental Disorders in Childhood and Adolescence via self-assessment (DISYPS Self) [n=441], and parent-assessment (DISYPS Proxy) [n=422]. Overall, 43.2% [n=201] were at risk for vitamin D deficiency (<30nmol/L), and 73.5%-83.2% –depending on assessment tool– showed at least mild depression. Linear regression revealed an inverse association between 25(OH)D and BDI-II in both crude and CRP-adjusted full-sample models. Logistic regressions showed a robust inverse association between 25(OH)D and DISYPS Proxy, but not for DISYPS Self. Although 25(OH)D was inversely correlated with some pro-inflammatory markers, neither their inclusion in regression models nor formal mediation analyses supported inflammation as a mediator of the vitamin D–depression association. Overall, our results suggest that vitamin D relates modestly to both depression and inflammation in adolescence. However, based on the measured parameters, we cannot confirm that anti-inflammatory effects are the link between vitamin D and depression.

Correction to: Changes in patterns of eating habits and food intake during the first German COVID-19 lockdown: results of a cross-sectional online survey - Bühlmeier, Judith; Frölich, Stefanie; Ludwig, Christine; Knoll-Pientka, Nadja; Schmidt, Börge; Föcker, Manuel; Libuda, Lars (European Journal of Nutrition)
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Age at menarche relates to depression in adolescent girls: Comparing a clinical sample to the general pediatric population - Hirtz, Raphael; Libuda, Lars; Hinney, Anke; Föcker, Manuel; Bühlmeier, Judith; Holterhus, Paul-Martin; Kulle, Alexandra; Kiewert, Cordula; Kuhnert, Ronny; Cohrdes, Caroline; Peters, Triinu; Hebebrand, Johannes; et al. (Journal of Affective Disorders)
Keywords: Psychiatry and Mental health; Clinical Psychology

Changes in patterns of eating habits and food intake during the first German COVID-19 lockdown: results of a cross-sectional online survey - Bühlmeier, Judith; Frölich, Stefanie; Ludwig, Christine; Knoll-Pientka, Nadja; Schmidt, Börge; Föcker, Manuel; Libuda, Lars (European Journal of Nutrition)
Abstract Purpose The COVID-19 pandemic and public measures have a direct impact on the nutrition situation; studies show changes in food consumption, eating behavior or body weight but complex pattern analyses of changes rarely exist. Methods During the first German lockdown, a web-based survey was conducted among adults. It included 33 questions about changes in food intake, eating habits and physical activity, as well as anthropometrics and sociodemographic factors. Patterns of change were calculated based on changes in food intake and eating habits using two-step cluster analysis. To identify influencing factors for assignment to the patterns of change, binary logistic regression analyses were performed. Results Data from 2103 participants (81% female, 40 ± 14 years) were considered for analysis. Increased stockpiling, cooking, and variation in preparation was reported by 50–70%. The constant pattern (C-P, 36%) reported little change besides the above. The health-oriented pattern (HO-P; 37%) reported eating more healthy foods, avoiding unhealthy foods, and eating less and less frequently. The emotional-driven pattern (ED-P; 28%) exhibits higher influence of emotions on eating behavior, less avoidance of unhealthy foods, and increased consumption of sweets, pastries, and alcohol. The odds of changing eating behavior either to HO-P or ED-P were higher in women, people with migration background, younger participants, and increased with BMI categories. Conclusion Both, the ED-P and HO-P, exhibit distinctive reactions in eating habits and food intake when dealing with a distressing experience. In subgroups, these may lead to disturbances in eating behavior and increase the risk for eating disorders and obesity.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Low leptin levels are associated with elevated physical activity among lean school children in rural Tanzania - Ludwig, Christine; Knoll-Pientka, Nadja; Mwanri, Akwilina; Erfle, Celina; Onywera, Vincent; Tremblay, Mark S.; Bühlmeier, Judith; Luzak, Agnes; Ferland, Maike; Schulz, Holger; Libuda, Lars; Hebebrand, Johannes (BMC Public Health)
Abstract Background In Sub-Saharan African countries, rapid urbanization and increasing socio-economic status are associated with a transition to decreased physical activity (PA). A more sedentary lifestyle is linked to increased body fat leading to increments in leptin levels. Since rodent and human studies in high-income countries have shown that starvation-induced hypoleptinemia triggers high PA, efforts are warranted to pursue the hypothesis that low leptin levels in lean children of low- and middle-income countries (LMIC) are also associated with high PA. Methods In this cross-sectional study, we assessed seven-day PA with triaxial accelerometry (ActiGraph GT3X) among 223 primary school children (9 to 12 years of age) in rural Tanzania. Moderate-to-vigorous PA (MVPA) and total accelerometer counts per day were outcome variables. Leptin was determined using enzyme linked immunosorbent assay tests from dried blood spots. Anthropometric assessments were conducted and food insecurity and socio-demographic data were gathered using semi-structured interviews. Results In this sample of school children in rural Tanzania, leptin concentrations (median: 0.91 ng/mL, P25: 0.55, P75: 1.69), body mass index z-scores (median: -1.35, P25: -1.93, P75: -0.82), and height-for-age-z-scores (median: -1.16, P25: -1.96, P75: -0.61) were low. In contrast, PA levels were high with a median MVPA time of 119 min/day. Linear regression confirmed that leptin levels were negatively associated with MVPA (beta: -18.1; 95%CI: -29.7; -6.5; p = 0.002) and total accelerometer counts (beta: -90,256; 95%CI: -154,146; -26,365; p = 0.006). Children residing in areas with better infrastructure had lower MVPA levels ( p < 0.001) and tended to have higher leptin levels ( p = 0.062) than children residing in areas only reachable via dirt roads. Conclusion Our cross-sectional field study is the first that supports the hypothesis of low leptin levels as a potential endocrine trigger of high PA in lean children of a LMIC. We observed early signs of a PA transition towards a less active lifestyle in a subgroup residing in areas with better infrastructure that concomitantly tended to have higher leptin concentrations. Considering that area-dependent PA differences were more pronounced among girls than boys, whereas differences in leptin levels were less pronounced, not only biological, but also external factors explain PA transition.
Keywords: Public Health; Environmental and Occupational Health

Obesogenic eating behaviour and dietary intake in German children and adolescents: results from the GINIplus and LISA birth cohort studies - Marb, Anne; Libuda, Lars; Standl, Marie; Koletzko, Sibylle; Bauer, Carl-Peter; Schikowski, Tamara; Berdel, Dietrich; von Berg, Andrea; Herberth, Gunda; Bühlmeier, Judith; Harris, Carla P. (European Journal of Clinical Nutrition)
Abstract Background/objectives The transition to adolescence is characterised by considerable behavioural changes, including diet. This study describes the level of obesogenic eating behaviours in 10- and 15-year-olds, and their association with dietary intake. Subjects/methods Participants of the 10- and 15-year follow-ups of the German GINIplus and LISA birth cohort studies were included (N 10 = 2257; N 15 = 1880). Eating behaviours and dietary intake were assessed via self-report questionnaires. Sex-stratified, cross-sectional associations of “external eating”, “emotional eating” and “dietary restraint” (the latter at age 15 years only) with dietary intake (17 food groups—categorised into tertiles, macronutrients, and total energy) were assessed using multinomial logistic or multiple linear regression as required, adjusting for covariates and correcting for multiple testing. Results Reported levels of eating behaviours were low in both age-groups. External eating was higher in 10-year-old males than females, while all eating behaviours were most pronounced in 15-year-old females. At 10 years, emotional eating was associated with medium vegetable intake in females (Relative Risk Ratio (RRR) = 1.84, p = 0.0017). At 15 years, external eating was associated with total energy (kJ) in females ( β = 718, p = 0.0002) and high butter intake in males (RRR = 1.96, p = 0.0019). Dietary restraint in females was inversely associated with total energy ( β = −967, p < 0.0001) and omega-3 fatty acids (Means Ratio (MR) = 0.94, p = 0.0017), and positively associated with high fruit (RRR = 2.20, p = 0.0003) and whole grains (RRR = 1.94, p = 0.0013). Conclusion Obesogenic eating behaviour scores are low among children and adolescents of a predominantly high socioeconomic status population and present only few associations with specific aspects of diet, mainly among adolescent females.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

The adrenal steroid profile in adolescent depression: a valuable bio-readout? - Hirtz, Raphael; Libuda, Lars; Hinney, Anke; Föcker, Manuel; Bühlmeier, Judith; Holterhus, Paul-Martin; Kulle, Alexandra; Kiewert, Cordula; Hauffa, Berthold P.; Hebebrand, Johannes; Grasemann, Corinna (Translational Psychiatry)
Abstract There is preliminary evidence that adrenal steroids other than cortisol may be valuable biomarkers for major depressive disorder (MDD). So far, studies have been conducted in adults only, and conclusions are limited, mainly due to small sample sizes. Therefore, the present study assessed whether adrenal steroids serve as biomarkers for adolescent MDD. In 261 depressed adolescents (170 females) treated at a single psychiatric hospital, serum adrenal steroids (progesterone, 17-hydroxyprogesterone, 21-deoxycortisol, 11-deoxycortisol, cortisol, cortisone, deoxycorticosterone, corticosterone) were determined by liquid chromatography-tandem mass spectrometry. Findings were compared to that of an age- and sex-matched reference cohort ( N = 255) by nonparametric analysis of variance. Nonparametric receiver operating characteristics (ROC) analyses were conducted to evaluate the diagnostic performance of single steroids and steroid ratios to classify depression status. Sensitivity analyses considered important confounders of adrenal functioning, and ROC results were verified by cross-validation. Compared to the reference cohort, levels of deoxycorticosterone and 21-deoxycortisol were decreased ( P < 0.001). All other glucocorticoid- and mineralocorticoid-related steroids were increased ( P < 0.001). The corticosterone to deoxycorticosterone ratio evidenced excellent classification characteristics, especially in females (AUC: 0.957; sensitivity: 0.902; specificity: 0.891). The adrenal steroid metabolome qualifies as a bio-readout reflecting adolescent MDD by a distinct steroid pattern that indicates dysfunction of the hypothalamus–pituitary–adrenal axis. Moreover, the corticosterone to deoxycorticosterone ratio may prospectively qualify to contribute to precision medicine in psychiatry by identifying those patients who might benefit from antiglucocorticoid treatment or those at risk for recurrence when adrenal dysfunction has not resolved.
Keywords: Biological Psychiatry; Cellular and Molecular Neuroscience; Psychiatry and Mental health

Vitamin D Level Trajectories of Adolescent Patients with Anorexia Nervosa at Inpatient Admission, during Treatment, and at One Year Follow Up: Association with Depressive Symptoms - Föcker, Manuel; Timmesfeld, Nina; Bühlmeier, Judith; Zwanziger, Denise; Führer, Dagmar; Grasemann, Corinna; Ehrlich, Stefan; Egberts, Karin; Fleischhaker, Christian; Wewetzer, Christoph; Wessing, Ida; Seitz, Jochen; et al. (Nutrients)
(1) Background: Evidence has accumulated that patients with anorexia nervosa (AN) are at higher risk for vitamin D deficiency than healthy controls. In epidemiologic studies, low 25(OH) vitamin D (25(OH)D) levels were associated with depression. This study analyzed the relationship between 25(OH)D serum levels in adolescent patients and AN and depressive symptoms over the course of treatment. (2) Methods: 25(OH)D levels and depressive symptoms were analyzed in 93 adolescent (in-)patients with AN from the Anorexia Nervosa Day patient versus Inpatient (ANDI) multicenter trial at clinic admission, discharge, and 1 year follow up. Mixed regression models were used to analyze the relationship between 25(OH)D levels and depressive symptoms assessed by the Beck Depression Inventory (BDI-II). (3) Results: Although mean 25(OH)D levels constantly remained in recommended ranges (≥50 nmol/L) during AN treatment, levels decreased from (in)patient admission to 1 year follow up. Levels of 25(OH)D were neither cross-sectionally, prospectively, nor longitudinally associated with the BDI-II score. (4) Conclusions: This study did not confirm that 25(OH)D levels are associated with depressive symptoms in patients with AN. However, increasing risks of vitamin D deficiency over the course of AN treatment indicate that clinicians should monitor 25(OH)D levels.

Alterations in B cell subsets correlate with body composition parameters in female adolescents with anorexia nervosa - Freff, Jana; Schwarte, Kathrin; Bröker, Lisa; Bühlmeier, Judith; Kraft, Isabelle; Öztürk, Dana; Hinney, Anke; Arolt, Volker; Dannlowski, Udo; Romer, Georg; Baune, Bernhard T.; Hebebrand, Johannes; et al. (Scientific Reports)
Abstract Anorexia nervosa (AN) is a severe eating disorder and often associated with altered humoral immune responses. However, distinct B cell maturation stages in peripheral blood in adolescents with AN have not been characterized. Treatment effects and the relationship between clinical and B cell parameters are also not fully understood. Here we investigated the phenotype of circulating B cell subsets and the relationship with body composition in adolescents with AN before (T0, n = 24) and after 6 weeks (T1, n = 20) of treatment. Using multi-parameter flow cytometry, we found increased percentages of antigen-experienced B cells and plasmablasts in patients with AN compared to healthy controls (n = 20). In contrast, percentages of CD1d + CD5 + B cells and transitional B cells with immunoregulatory roles were reduced at T0 and T1. These B cell frequencies correlated positively with fat mass, fat mass index (FMI), free fat mass index, and body mass index standard deviation score. In addition, scavenger-like receptor CD5 expression levels were downregulated on transitional B cells and correlated with fat mass and FMI in AN. Our findings that regulatory B cell subgroups were reduced in AN and their strong relationship with body composition parameters point toward an impact of immunoregulatory B cells in the pathogenesis of AN.

Kurzzeitige Behandlung von Patient_innen mit Anorexia nervosa mit rekombinant hergestelltem Human-Leptin (Metreleptin): Rasch einsetzende positive Effekte auf Stimmung, Kognition und Verhalten - Hebebrand, Johannes; Antel, Jochen; Tan, Susanne; Wabitsch, Martin; Wiesing, Urban; Barth, Nikolaus; Ludwig, Christine; Bühlmeier, Judith; Libuda, Lars; Milos, Gabriella; Hinney, Anke (Zeitschrift für Kinder- und Jugendpsychiatrie und Psychotherapie)

Effect of vitamin D deficiency on depressive symptoms in child and adolescent psychiatric patients: results of a randomized controlled trial - Libuda, Lars; Timmesfeld, Nina; Antel, Jochen; Hirtz, Raphael; Bauer, Jens; Führer, Dagmar; Zwanziger, Denise; Öztürk, Dana; Langenbach, Gina; Hahn, Denise; Ring, Stefanie; Peters, Triinu; et al. (European Journal of Nutrition)
Abstract Purpose While observational studies revealed inverse associations between serum vitamin D levels [25(OH)D] and depression, randomized controlled trials (RCT) in children and adolescents are lacking. This RCT examined the effect of an untreated vitamin D deficiency compared to an immediate vitamin D 3 supplementation on depression scores in children and adolescents during standard day and in-patient psychiatric treatment. Methods Patients with vitamin D deficiency [25(OH)D ≤ 30 nmol/l] and at least mild depression [Beck Depression Inventory II (BDI-II) > 13] ( n = 113) were 1:1 randomized into verum (VG; 2640 IU vitamin D 3 /d) or placebo group (PG) in a double-blind manner. During the intervention period of 28 days, both groups additionally received treatment as usual. BDI-II scores were assessed as primary outcome, DISYPS-II (Diagnostic System for Mental Disorders in Childhood and Adolescence, Self- and Parent Rating) and serum total 25(OH)D were secondary outcomes. Results At admission, 49.3% of the screened patients ( n = 280) had vitamin D deficiency. Although the intervention led to a higher increase of 25(OH)D levels in the VG than in the PG (treatment difference: + 14 ng/ml; 95% CI 4.86–23.77; p = 0.003), the change in BDI-II scores did not differ (+ 1.3; 95% CI − 2.22 to 4.81; p = 0.466). In contrast, DISYPS parental ratings revealed pronounced improvements of depressive symptoms in the VG (− 0.68; 95% CI − 1.23 to − 0.13; p = 0.016). Conclusion Whereas this study failed to show a vitamin D supplementation effect on self-rated depression in adolescent in- or daycare patients, parents reported less depressive symptoms in VG at the end of our study. Future trials should consider clinician-rated depressive symptoms as primary outcome. Trial registration “German Clinical Trials Register” ( https://www.drks.de ), registration number: DRKS00009758

Effects of 21 days of bed rest and whey protein supplementation on plantar flexor muscle fatigue resistance during repeated shortening contractions - Bosutti, Alessandra; Mulder, Edwin; Zange, Jochen; Bühlmeier, Judith; Ganse, Bergita; Degens, Hans (European Journal of Applied Physiology)
Abstract Purpose Space flight and bed rest (BR) lead to a rapid decline in exercise capacity. Whey protein plus potassium bicarbonate diet-supplementation (NUTR) could attenuate this effect by improving oxidative metabolism. We evaluated the impact of 21-day BR and NUTR on fatigue resistance of plantar flexor muscles (PF) during repeated shortening contractions, and whether any change was related to altered energy metabolism and muscle oxygenation. Methods Ten healthy men received a standardized isocaloric diet with ( n = 5) or without ( n = 5) NUTR. Eight bouts of 24 concentric plantar flexions (30 s each bout) with 20 s rest between bouts were employed. PF muscle size was assessed by means of peripheral quantitative computed tomography. PF muscle volume was assessed with magnetic resonance imaging. PF muscle force, contraction velocity, power and surface electromyogram signals were recorded during each contraction, as well as energy metabolism ( 31 P nuclear magnetic resonance spectroscopy) and oxygenation (near-infrared spectroscopy). Cardiopulmonary parameters were measured during an incremental cycle exercise test. Results BR caused 10–15% loss of PF volume that was partly recovered 3 days after re-ambulation, as a consequence of fluid redistribution. Unexpectedly, PF fatigue resistance was not affected by BR or NUTR. BR induced a shift in muscle metabolism toward glycolysis and some signs of impaired muscle oxygen extraction. NUTR did not attenuate the BR-induced-shift in energy metabolism. Conclusions Twenty-one days’ BR did not impair PF fatigue resistance, but the shift to glycolytic metabolism and indications of impaired oxygen extraction may be early signs of developing reduced muscle fatigue resistance.
Keywords: Physiology (medical); Public Health; Environmental and Occupational Health; Orthopedics and Sports Medicine; General Medicine; Public Health; Environmental and Occupational Health; Physiology

Evaluation of Metabolic Profiles of Patients with Anorexia Nervosa at Inpatient Admission, Short- and Long-Term Weight Regain—Descriptive and Pattern Analysis - Föcker, Manuel; Cecil, Alexander; Prehn, Cornelia; Adamski, Jerzy; Albrecht, Muriel; Adams, Frederike; Hinney, Anke; Libuda, Lars; Bühlmeier, Judith; Hebebrand, Johannes; Peters, Triinu; Antel, Jochen (Metabolites)
Acute anorexia nervosa (AN) constitutes an extreme physiological state. We aimed to detect state related metabolic alterations during inpatient admission and upon short- and long-term weight regain. In addition, we tested the hypothesis that metabolite concentrations adapt to those of healthy controls (HC) after long-term weight regain. Thirty-five female adolescents with AN and 25 female HC were recruited. Based on a targeted approach 187 metabolite concentrations were detected at inpatient admission (T0), after short-term weight recovery (T1; half of target-weight) and close to target weight (T2). Pattern hunter and time course analysis were performed. The highest number of significant differences in metabolite concentrations (N = 32) were observed between HC and T1. According to the detected main pattern, metabolite concentrations at T2 became more similar to those of HC. The course of single metabolite concentrations (e.g., glutamic acid) revealed different metabolic subtypes within the study sample. Patients with AN after short-term weight regain are in a greater “metabolic imbalance” than at starvation. After long-term weight regain, patients reach a metabolite profile similar to HC. Our results might be confounded by different metabolic subtypes of patients with AN.

Vitamin D and the Risk of Depression: A Causal Relationship? Findings from a Mendelian Randomization Study - Libuda, Lars; Laabs, Björn-Hergen; Ludwig, Christine; Bühlmeier, Judith; Antel, Jochen; Hinney, Anke; Naaresh, Roaa; Föcker, Manuel; Hebebrand, Johannes; König, Inke R.; Peters, Triinu (Nutrients)
While observational studies show an association between 25(OH)vitamin D concentrations and depressive symptoms, intervention studies, which examine the preventive effects of vitamin D supplementation on the development of depression, are lacking. To estimate the role of lowered 25(OH)vitamin D concentrations in the etiology of depressive disorders, we conducted a two-sample Mendelian randomization (MR) study on depression, i.e., “depressive symptoms” (DS, n = 161,460) and “broad depression” (BD, n = 113,769 cases and 208,811 controls). Six single nucleotide polymorphisms (SNPs), which were genome-wide significantly associated with 25(OH)vitamin D concentrations in 79,366 subjects from the SUNLIGHT genome-wide association study (GWAS), were used as an instrumental variable. None of the six SNPs was associated with DS or BD (all p > 0.05). MR analysis revealed no causal effects of 25(OH)vitamin D concentration, either on DS (inverse variance weighted (IVW); b = 0.025, SE = 0.038, p = 0.52) or on BD (IVW; b = 0.020, SE = 0.012, p = 0.10). Sensitivity analyses confirmed that 25(OH)vitamin D concentrations were not significantly associated with DS or BD. The findings from this MR study indicate no causal relationship between vitamin D concentrations and depressive symptoms, or broad depression. Conflicting findings from observational studies might have resulted from residual confounding or reverse causation.

Risk factors for a low weight gain in the early stage of adolescent anorexia nervosa inpatient treatment: findings from a pilot study - Knoll-Pientka, Nadja; Bühlmeier, Judith; Peters, Triinu; Albrecht, Muriel; Adams, Frederike; Wustrau, Katharina; Teufel, Martin; Hebebrand, Johannes; Föcker, Manuel; Libuda, Lars (Eating and Weight Disorders - Studies on Anorexia, Bulimia and Obesity)

Clinical Trials Required to Assess Potential Benefits and Side Effects of Treatment of Patients With Anorexia Nervosa With Recombinant Human Leptin - Hebebrand, Johannes; Milos, Gabriella; Wabitsch, Martin; Teufel, Martin; Führer, Dagmar; Bühlmeier, Judith; Libuda, Lars; Ludwig, Christine; Antel, Jochen (Frontiers in Psychology)

Retrospektive Evaluation der Umsetzung einer klinikinternen Handlungsanweisung zur Ernährungstherapie von Intensivpatienten - Dresen, Ellen; Weißbrich, Carsten; Bühlmeier, Judith; Weisheit, Christina; Egert, Sarah; Putensen, Christian; Stehle, Peter (Aktuelle Ernährungsmedizin)
Zusammenfassung Hintergrund Die begleitende Ernährungstherapie von Intensivpatienten stellt eine besondere Herausforderung in der klinischen Routine dar und erfordert die Implementation von leitlinienbasierten Handlungsanweisungen. Methoden In einer retrospektiven Analyse wurde die Umsetzung der klinikinternen Handlungsanweisung zur Ernährung kritisch kranker Patienten (Gültigkeitszeitraum September 2013 bis Januar 2016) sowie der Anordnung zur Ernährungstherapie auf einer operativen Intensivstation des Universitätsklinikums Bonn an Daten des Ernährungsmanagements von 31 Langzeit-Intensivpatienten (7 Frauen; Alter: 60 ± 17 Jahre; BMI: 28 ± 10 kg/m2; Dauer des Intensivaufenthalts: 34 ± 16 Tage) evaluiert. Ausgewertet wurden Daten zur Initiation, zum Ablauf sowie zur Berechnung und Umsetzung der Energie- und Proteinzufuhr. Dazu wurden jeweils die im Stationsalltag angeordnete bzw. protokollierte Zufuhr, die protokollierte Zufuhr abzüglich Reflux sowie das retrospektiv beurteilte Ziel, welches durch die klinikinterne Handlungsanweisung indiziert war, miteinander verglichen (linear gemischtes Modell). Ergebnisse Mit der enteralen Ernährung wurde im Mittel an Tag 4 ± 3, mit der (supplementierenden) parenteralen an Tag 3 ± 3 begonnen. Die Energiezufuhr wurde mit Korrekturfaktoren als ein Vielfaches des Grundumsatzes nach Harris & Benedict berechnet. Der individuell verwendete Korrekturfaktor zur Berechnung der angeordneten Energiezufuhr wich über die gesamte Dauer des stationären Aufenthalts 0,1 ± 0,3 vom retrospektiv als angemessen erachteten Korrekturfaktor ab. Hieraus resultierte eine Abweichung der angeordneten Energiezufuhr vom Energieziel von 123 ± 528 kcal/24 h. Insbesondere in den Tagen 1 – 10 betrug die Abweichung des angeordneten vom retrospektiv als angemessen erachteten Korrekturfaktor 0,2 ± 0,4, was zu einer Differenz zwischen angeordneter Energiezufuhr und Energieziel von 426 ± 772 kcal/24 h führte. Die protokollierte Proteinzufuhr lag über die gesamte Behandlungsdauer bei 1,1 g/kg KG/24 h, während das retrospektiv ermittelte Proteinziel 1,0 g/kg KG/24 h betrug. Schlussfolgerung Die Analyse liefert vertrauenswürdige Daten zur Implementation einer individualisierten Ernährungstherapie von Langzeit-Intensivpatienten auf einer operativen Intensivstation; diese können zur Weiterentwicklung von entsprechenden Handlungsanweisungen genutzt werden. Defizite bestehen sowohl im zeitlichen Ablauf (zu später Beginn) als auch in der Anordnung der Energie-/Nährstoffzufuhr. Umfassende Schulungen des ärztlichen und pflegerischen Personals zur Anwendung/Umsetzung der Ernährungstherapie sind zu empfehlen.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

The negative effect of unloading exceeds the bone-sparing effect of alkaline supplementation: a bed rest study - Frings-Meuthen, P.; Bernhardt, G.; Bühlmeier, Judith; Baecker, N.; May, F.; Heer, M. (Osteoporosis International)
Keywords: Endocrinology; Diabetes and Metabolism

Metabolic Inflexibility Is an Early Marker of Bed-Rest–Induced Glucose Intolerance Even When Fat Mass Is Stable - Rudwill, Floriane; O’Gorman, Donal; Lefai, Etienne; Chery, Isabelle; Zahariev, Alexandre; Normand, Sylvie; Pagano, Allan F; Chopard, Angèle; Damiot, Anthony; Laurens, Claire; Hodson, Leanne; Canet-Soulas, Emmanuelle; et al. (The Journal of Clinical Endocrinology & Metabolism)
Abstract Context The effects of energy-balanced bed rest on metabolic flexibility have not been thoroughly examined. Objective We investigated the effects of 21 days of bed rest, with and without whey protein supplementation, on metabolic flexibility while maintaining energy balance. We hypothesized that protein supplementation mitigates metabolic inflexibility by preventing muscle atrophy. Design and Setting Randomized crossover longitudinal study conducted at the German Aerospace Center, Cologne, Germany. Participants and Interventions Ten healthy men were randomly assigned to dietary countermeasure or isocaloric control diet during a 21-day bed rest. Outcome Measures Before and at the end of the bed rest, metabolic flexibility was assessed during a meal test. Secondary outcomes were glucose tolerance by oral glucose tolerance test, body composition by dual energy X-ray absorptiometry, ectopic fat storage by magnetic resonance imaging, and inflammation and oxidative stress markers. Results Bed rest decreased the ability to switch from fat to carbohydrate oxidation when transitioning from fasted to fed states (i.e., metabolic inflexibility), antioxidant capacity, fat-free mass (FFM), and muscle insulin sensitivity along with greater fat deposition in muscle (P < 0.05 for all). Changes in fasting insulin and inflammation were not observed. However, glucose tolerance was reduced during acute overfeeding. Protein supplementation did not prevent FFM loss and metabolic alterations. Conclusions Physical inactivity triggers metabolic inflexibility, even when energy balance is maintained. Although reduced insulin sensitivity and increased fat deposition were observed at the muscle level, systemic glucose intolerance was detected only in response to a moderately high-fat meal. This finding supports the role of physical inactivity in metabolic inflexibility and suggests that metabolic inflexibility precedes systemic glucose intolerance.
Keywords: Biochemistry (medical); Clinical Biochemistry; Endocrinology; Biochemistry; Endocrinology; Diabetes and Metabolism